2017
DOI: 10.1051/sicotj/2017011
|View full text |Cite
|
Sign up to set email alerts
|

A mid-term follow-up of Koutsogiannis’ osteotomy in adult-acquired flatfoot stage II and “early stage III”

Abstract: Introduction: Koutsogiannis’ osteotomy has been widely described to treat adult-acquired flatfoot. However, few articles describe its midterm follow-up. Our aim was to study clinical and radiological outcomes at least one year after surgery and to analyze whether a combined procedure on the medial soft tissue affected these outcomes. Methods: We performed a retrospective study of 30 feet of patients who underwent a Koutsogiannis’ osteotomy due to adult-acquired flatfoot stage II and “early stage III”: a stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hindfoot arthritis are the next stage for these patients. Performing the calcaneal medializing correction can avoid this evolution (13,16,19). So, the best time to perform the procedure is after deformity but before arthritis, which means that the patient should be addressed in a lifetime when short recovery procedures are fundamental for early return to work, your understanding is that minimally invasive corrections will play a fundamental role in this new reality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hindfoot arthritis are the next stage for these patients. Performing the calcaneal medializing correction can avoid this evolution (13,16,19). So, the best time to perform the procedure is after deformity but before arthritis, which means that the patient should be addressed in a lifetime when short recovery procedures are fundamental for early return to work, your understanding is that minimally invasive corrections will play a fundamental role in this new reality.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent evidence has shown that in many cases, the disease starts as a ligamental insufficiency and the healthy tibialis posterior reacts trying to compensate and in a later pathology moment degenerate. (1,5,8,10) This new understanding led to surgeries to address ligament reconstruction preserving tibialis posterior (1,3,5,6,8) or isolated calcaneal osteotomies to give a better leaver arm for the tendon function (11,12,13). Minimally invasive calcaneal osteotomy is one possible technique for flat foot correction with many possible advantages are earlier weight bearing and earlier consolidation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations